An analysis of racial inequities in emergency department triage among patients with stroke-like symptoms in the United States - Gabriel Neves; John DeToledo; James Morris; K. Tom Xu (BMC Emergency Medicine, 2023)
Abstract Background Racial inequities exist in treatment and outcomes in patients with acute stroke. Objectives Our objective was to determine if racial inequities exist in the time-lapse between patient presentation and provider assessment in patients with stroke-like symptoms in Emergency Departments (ED) across the U.S. Methods This study is a retrospective, observational study of the National Hospital Ambulatory Medical Care Survey (NHAMCS) 2014–2018. We identified visits with stroke-like symptoms and stratified the proportion of door-to-provider (DTP) times by racial groups. We used broad and narrow definitions of stroke-like symptoms. We performed bivariate and multivariate analyses using race and clinical and demographic characteristics as covariates. Results Between 2014–2018, there were an average of 138.58 million annual ED visits. Of the total ED visits, 0.36% to 7.39% of the ED visits presented with stroke-like symptoms, and the average DTP time ranged from 39 to 49 min. The proportion of the visits with a triage level of 1 (immediate) or 2 (emergent) ranged from 16.03% to 23.27% for stroke-like symptoms. We did not find statistically significant racial inequities in DTP or ED triage level. We found significantly longer DTP times in non-Hispanic blacks (15.88 min, 95% CI: 4.29–27.48) and Hispanics (by 14.77 min, 95% CI: 3.37–26.16) than non-Hispanic whites that presented with atypical stroke-like symptoms. We observed that non-Hispanic whites were significantly more diagnosed with a stroke/TIA than other racial minority groups (p = 0.045) for atypical stroke-like symptoms. Conclusion In our population-based analysis, we did not identify systemic racial inequities in the DTP times or ED triage level at ED triage for stroke-like symptoms.